Hometown Tax as Crowdfunding: - Shuji Ohira; Sumire Stanislawski; Yuichiro Hidaka; Kosuke Mizukoshi (Maketingu Janaru, 2021)
The hometown tax is a new tax payment scheme introduced in Japan in 2008 that aims to redistribute taxes that have tended to concentrate in urban centers such as Tokyo. This scheme has seen very rapid growth since 2015 when documents to be submitted for tax returns were made simpler. Previous studies of hometown tax have focused on case analyses, and there is a lack of development of analytical frameworks and insights into its users. Hence, this study aims to increase understanding of this scheme as donation-based and reward-based crowdfunding with users acting as donors and consumers, along with their motivations to participate. First, this research considers the motivations of donors and consumers by reviewing prior research on charitable giving and cause-related marketing. Second, a conceptual framework for understanding donors and consumers who utilize hometown tax is developed. Finally, this study indicates practical marketing implications for local governments.